2013
DOI: 10.1371/journal.pone.0062251
|View full text |Cite
|
Sign up to set email alerts
|

TnaA, an SP-RING Protein, Interacts with Osa, a Subunit of the Chromatin Remodeling Complex BRAHMA and with the SUMOylation Pathway in Drosophila melanogaster

Abstract: Tonalli A (TnaA) is a Drosophila melanogaster protein with an XSPRING domain. The XSPRING domain harbors an SP-RING zinc-finger, which is characteristic of proteins with SUMO E3 ligase activity. TnaA is required for homeotic gene expression and is presumably involved in the SUMOylation pathway. Here we analyzed some aspects of the TnaA location in embryo and larval stages and its genetic and biochemical interaction with SUMOylation pathway proteins. We describe that there are at least two TnaA proteins (TnaA13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…2B). Three of the validated proteins have been previously identified as SUMOylated proteins: Ultraspiracle (Usp), a nuclear receptor involved in steroid signalling46, the transcription factor Osa3747, the intermediate filament Lamin (Lam, also a key nuclear envelope component)38 and the eukaryotic initiation factor 4E (eIF-4E)48. One of the validated proteins was not previously described to be SUMOylated in Drosophila , the Glutathione S-transferase involved in axonogenesis Failed axon connections (Fax), and thus is the first Fax homolog to be identified as a target of SUMOylation.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Three of the validated proteins have been previously identified as SUMOylated proteins: Ultraspiracle (Usp), a nuclear receptor involved in steroid signalling46, the transcription factor Osa3747, the intermediate filament Lamin (Lam, also a key nuclear envelope component)38 and the eukaryotic initiation factor 4E (eIF-4E)48. One of the validated proteins was not previously described to be SUMOylated in Drosophila , the Glutathione S-transferase involved in axonogenesis Failed axon connections (Fax), and thus is the first Fax homolog to be identified as a target of SUMOylation.…”
Section: Resultsmentioning
confidence: 99%
“…Brd2/Ring3, a human counterpart of the Drosophila trxG gene fsh, encodes a nuclear protein kinase with two bromodomains, implicated in cell-cycle progression and leukemogenesis, but the substrates of the kinase are currently unknown (Denis and Green 1996). The trxG gene Tonalli (Tna) encodes a protein related to SP-RING finger proteins involved in sumoylation, suggesting that it may regulate transcription via the covalent modification of proteins other than histones (Gutierrez et al 2003;Monribot-Villanueva et al 2013). The trxG gene sallimus (sls) was identified in a screen for extragenic suppressors of Pc and subsequently found to encode Drosophila Titin (Machado and Andrew 2000).…”
Section: Biochemical Functions Of Other Trxg Proteinsmentioning
confidence: 99%
“…Notably, two subunits of this module, Med12 and Med13 ( skuld and kohtalo respectively in Drosophila), were revealed both as trxG and PcG proteins in different genetic screenings designed to identify factors required to maintain the activation or the repression of Hox genes (Gaytán de Ayala et al, ; Kennison & Tamkun, ). So far, these two subunits have not been found SUMOylated in global analyses but they do interact genetically with TnaA, another trxG protein with a putative SUMO E3 ligase activity (see ahead) (Gutiérrez, Zurita, Kennison, & Vázquez, ; Monribot‐Villanueva et al, ).…”
Section: Promoters and Sumoylation Of Basal Transcription Factorsmentioning
confidence: 99%
“…In humans, the Brm‐related protein BRG1 (Hendriks & Vertegaal, ), and the Drosophila BAP subunit Osa (Monribot‐Villanueva et al, ; Nie et al, ) have been found SUMOylated. At least one Osa function could be to recruit the BAP complex to chromatin of genes that are going to be activated (Eroglu et al, ; Vázquez, Moore, & Kennison, ).…”
Section: Sumoylation Of Trxg Proteinsmentioning
confidence: 99%
See 1 more Smart Citation